Polyostotic Fibrous Dysplasia Complicated by Pathological Fracture of Right Femoral Shaft with Nonunion: A Case Report - Yang, Qifan; Liu, Jing; Tan, Lei; Jiang, Ye; Zhu, Dong (Frontiers in Surgery, 2022)
Introduction: Fibrous dysplasia is a benign fibrous bone tumor that accounts for 5% to 10% of benign bone tumors. It can manifest as simple fibrous dysplasia (70% - 80%), polyostotic fibrous dysplasia (20% - 30%), with approximately the same incidence in men and women(1). We report a patient with a rare case of multiple fibrous dysplasia combined with proximal femoral shepherd deformity with pathological fracture of the femoral shaft complicated by nonunion. It is necessary to understand the disease in more detail to avoid overtreatment of benign lesions or misdiagnosis of malignant tumors and other diseases. Case presentation: A 58-year-old man with polyostotic fibrous dysplasia, bilateral proximal femur deformity, Shepherd's angle deformity, right femoral shaft pathological fracture complicated by nonunion, we under fluoroscopy, in the obvious proximal fracture, take osteotomy, and process the shape of the cut bone fragment to adapt it to the corrected force line, and then restore it back to its original position, using intramedullary nailing technology complete the operation. Three months after the operation, he came to the hospital for re-examination, and an X-ray of the right femur was taken. It was found that the fractured end had a tendency to heal. The patient was instructed to gradually bear weight. After six months of re-examination, the patient could walk with a walker. One year after the operation, the patient could walk without a walker and take care of himself at home. However, there was still stretch-like pain in the right lower back, but it was tolerable. Conclusions: For patients with polyostotic fibrous dysplasia combined with proximal femoral shepherd deformity and pathological fracture of the femoral shaft with nonunion, osteotomy combined with intramedullary nailing is a simple and convenient way to correct the deformity and obtain correct fracture alignment. Keywords: Fibrous dysplasia, Shepherd's crook deformity, Nonunion, Osteotomies, Femoral shaft fracture.